Review of MEMS Test Structures for Mechanical Parameter Extraction - A. Sharma; M. Kaur; D. Bansal; D. Kumar; K. Rangra (Журнал нано- та електронної фізики)
This paper reviews the recent progress in MEMS test structures for mechanical parameter extraction. MEMS test structures reviewed include cantilevers, fixed-fixed beams, bent-beam, guckel rings, pointers, circular diaphragm, and lancet structures. Important mechanical and process parameters are highlighted, as they have significant contributions to the performance of MEMS devices. The challenges and statues of the test structures are outlined and discussed.